Five New Triterpenoid Saponins from the Rhizomes of Panacis majoris and Their Antiplatelet Aggregation Activity - Li, Min; Liu, Fen; Jin, Yong-Ri; Wang, Xiao-Zhong; Wu, Qian; Liu, Ying; Li, Xu-Wen (Planta Medica, 2017)
Five new triterpenoid saponins (1–5) and four known triterpenoid saponins, ginsenoside Re5 (6), majonoside R1 (7), 24(R)-majonoside R1 (8), and ginsenoside Rf (9), were isolated from the rhizomes of Panacis majoris. The structures of new compounds were elucidated as (20S,24S,25R*)-6-O-[β-D-glucopyranosyl-(1 → 2)-β-D-glucopyranosyl]-dammar-20,24-epoxy-3β,6α,12β,25,26-pentaol (1), (20S,24R,25R)-6-O-[β-D-glucopyranosyl-(1 → 2)-β-D-glucopyranosyl]-dammar-20,24-epoxy-3β,6α,12β,25,26-pentaol (2), (20S)-6-O-[β-D-glucopyranosyl-(1 → 2)-β-D-glucopyranosyl]-dammar-20,25-epoxy-3β,6α,12β,24α-tetraol (3), 6-O-[β-D-glucopyranosyl-(1 → 2)-β-D-glucopyranosyl]-dammar-3β,6α,12β,20S,24R,25-hexaol (4), and 6-O-[β-D-glucop-yranosyl-(1 → 2)-β-D-glucopyranosyl]-dammar-25(26)-ene-3β,6α,12β,20S,24R-pentaol (5) on the basis of extensive spectral analysis and chemical methods. Ginsenoside Re5 was isolated from the plant for the first time. The similarities of the nine compounds lie in the fact that their aglycones are conjoined with the same glucopyranose moieties, the same linkage of the glycosyl chains, and the same glycosylation sites, while they have a varied C-17 side chain. Compounds 3 and 5 exhibited moderate antiplatelet aggregation activities induced by adenosine diphosphate with IC50 values of 23.24 and 18.43 µM, respectively. Compound 5 displayed moderate inhibition of arachidonic acid-induced platelet aggregation with an IC50 value of 30.11 µM.
Keywords: Panacis majoris; Araliaceae; triterpenoid saponins; antiplatelet aggregation